Pengembangan Media Pembelajaran Biologi Berupa E-Book Berbasis Mobile Learning Untuk Mata Kuliah Struktur Tumbuhan Pada Materi Batang Bagi Mahasiswa Biologi - Utomo, Arif Budi; Yelianti, Upik; Muswita, Muswita; Wicaksana, Ervan Johan (Bioedukasi: Jurnal Pendidikan Biologi, 2018)
Plant structure is one of the subjects in biology education program at Jambi University. Based on documentation of plant structure course value, in semester 2015/2016 is known that 64.47% of students have not achieved good grades. One material that is quite difficult is stem material, it is known that the number of foreign terms in the text book makes students feel difficult. One of the learning media that can be used is e-book, e-book contains electronic information in the form of text, images and audio packaged. This research aims to develop an ebook based android smartphone as biology learning media, also to determine the feasibility and response of students and lecturers to developed e-book. This study uses the ADDIE model with qualitative and quantitative data. In the validation step by media experts, the final percentage was 100%, the validation by the product experts gained a percentage of 89%. Furthermore, the product was tested on students consisting of 8 small groups and 24 large groups. The response of students in the small group trial got a percentage score of 89% with the criteria of "Very Good" while the large group received a percentage of 83.14% "Very Good". In the experiments conducted by lecturers, the course on plant structure obtained a percentage of 89% "Very Good". Thus it can be said that the media get a positive response and can be accepted in the learning process. Based on the research that has been done it is suggested that the media can be used when learning takes place or as an independent learning material for students so that it is easier to understand the material and can be used as a complementary learning material for lecturers on plant structure courses.